Dielectric properties of (1−x)Sr0.92La0.08TiO3-(x)CaMn0.98Nb0.02O3 ceramics under violet light irradiation - Panupong Jaiban (2018)
© 2017 (1−x)Sr0.92La0.08TiO3-(x)CaMn0.98Nb0.02O3 (SLTO-CMNO) ceramics with x = 0, 0.1, 0.2 and 0.3 were prepared employing a solid state sintering method. X-ray diffraction patterns and X-ray absorption spectra from synchrotron light indicated the substitution of CMNO in SLTO ceramic. Upon CMNO addition, existence of A and B-site vacancies was induced. When violet light irradiated the samples, oxygen vacancies were produced and in turn trapped by these cationic site vacancies, inducing defect dipoles. The dielectric enhancement under light stimulus was observed in correlation with defect dipoles. The results here suggested that photo-induced dielectric properties of SLTO may be largely tunable by CMNO addition, and SLTO-CMNO ceramics could be an alternative material for light sensor.